2008
DOI: 10.4049/jimmunol.180.9.5983
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation Regulates the Transcriptional Activity of JunB in T Lymphocytes

Abstract: The AP-1 family member JunB is a critical regulator of T cell function. JunB is a transcriptional activator of various cytokine genes, such as IL-2, IL-4, and IL-10; however, the post-translational modifications that regulate JunB activity in T cells are poorly characterized. We show here that JunB is conjugated with small ubiquitin-like modifier (SUMO) on lysine 237 in resting and activated primary T cells and T cell lines. Sumoylated JunB associated with the chromatin-containing insoluble fraction of cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 55 publications
3
44
0
1
Order By: Relevance
“…Ubc9 is an E2-conjugating enzyme that transfers the sumo protein to the acceptor lysine residue on the target protein (35). Expression of DN-Ubc9 (C93S and L97S) has been previously shown to inhibit sumoylation (36). In support of our data, another study showed the presence of modified forms of S100A4 in nuclear extracts of the colorectal cancer cell line SW620, suggesting the presence of post-translational modification (37).…”
Section: Discussionsupporting
confidence: 87%
“…Ubc9 is an E2-conjugating enzyme that transfers the sumo protein to the acceptor lysine residue on the target protein (35). Expression of DN-Ubc9 (C93S and L97S) has been previously shown to inhibit sumoylation (36). In support of our data, another study showed the presence of modified forms of S100A4 in nuclear extracts of the colorectal cancer cell line SW620, suggesting the presence of post-translational modification (37).…”
Section: Discussionsupporting
confidence: 87%
“…We also observed that JUNB deletion leads to decreased IL-2 production in T cells from ConA-or αGalCer-treated mice, consistent with in vitro experiments demonstrating that AP-1 modulates IL-2 transcription in T cells (18,19,47). IL-2 triggers NK cell proliferation and activation (48) and increases IFN-γ expression in T cells (49) and NK cells (48).…”
Section: Methodssupporting
confidence: 67%
“…To date, little information is available regarding a role of Ubc9 and, by extension, sumoylation in the immune system [29,30]. However, it has been reported that Ubc9 modulates the activity of some transcription factors that regulate inflammatory response, such as nuclear factor κB, and STAT1 [29,31,32].…”
Section: Discussionmentioning
confidence: 98%